A comparison of the average prekernel and the prekernel - Roberto Serrano; Ken-ichi Shimomura (Brown University, Department of Economics, 2001)
We propose positive and normative foundations for the average prekernel of NTU games, and compare them with the existing ones for the prekernel. In our non-cooperative analysis, the average prekernel is understood as the equilibrium payoffs of a game where each player faces the possibility of bargaining at random against any other player. In the kooperative analysis, we characterize the average prekernel as the unique solution that satisfies a set of Nash-like axioms for two-person games, and versions of average consistency and its converse for multilateral settings.
Keywords: C71; C72; C78; 330; average prekernel; prekernel; Nash set; Nash program; bargaining; consistency; average consistency; Core; Verhandlungstheorie; Spieltheorie; Theorie